Entrepreneurial Leadership: Strategies For Enhancing Team Performance and Business Growth - Erlangga, Heri; Hindarsah, Ida; Riani, Dini; Setiawati, Tita; Riadi, Farid (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
This research examines the importance of entrepreneurial leadership in improving team performance and business growth. The background to the problem shows that many companies face challenges in achieving optimal team performance and sustainable growth. Although various leadership models have been implemented, there is a gap in the literature exploring the specific strategies used by entrepreneurial leaders to overcome these challenges. The observed phenomenon shows that leaders with an entrepreneurial orientation tend to be more adaptive and innovative in facing market changes. The importance of this research lies in its in-depth qualitative approach to understanding the dynamics of entrepreneurial leadership. The method used involves in-depth interviews with business leaders who have proven success in improving team performance and driving business growth. The data collected was analyzed using a thematic approach to identify the main strategies implemented by these leaders. The research results show that entrepreneurial leaders use various strategies such as team empowerment, measured risk taking, and continuous innovation to improve team performance. In addition, they also emphasized the importance of a clear vision and effective communication to encourage team spirit and collaboration. Discussion of the results shows that these strategies not only improved team performance but also contributed to significant business growth. Thus, entrepreneurial leadership plays an important role in overcoming the challenges of team performance and business growth. This study provides valuable insights for business leaders and researchers into how entrepreneurial leadership strategies can be implemented effectively to achieve organizational goals.